2018
DOI: 10.1080/17429145.2018.1447698
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of MbWRKY2 gene involved in enhanced drought tolerance in transgenic tobacco

Abstract: Plant-specific WRKY transcription factors are widely involved in abiotic stress responses. In this study, a WRKY gene was isolated from Malus baccata (L.) Borkh and designated it as MbWRKY2. Subcellular localization showed that MbWRKY2 was localized in the nucleus. The expression levels of MbWRKY2 were up-regulated by abiotic stresses in M. baccata. When MbWRKY2 was introduced into tobacco, it improved drought stress tolerance in transgenic plants. The transgenic tobaccos had the higher contents of chlorophyl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The seedlings cultured under normal Hoagland nutrient solution were as control. After 0, 1, 3, 6, 12, 24 and 48 h for stress treatment, the plant materials were obtained and frozen with liquid nitrogen immediately, then stored in −80 • C for RNA extraction [35].…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…The seedlings cultured under normal Hoagland nutrient solution were as control. After 0, 1, 3, 6, 12, 24 and 48 h for stress treatment, the plant materials were obtained and frozen with liquid nitrogen immediately, then stored in −80 • C for RNA extraction [35].…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…These results showed that the WRKY TFs family was highly conserved during evolution (Rinerson et al 2015). Previous reports have indicated that WRKY TFs genes are widely distributed in Arabidopsis, rice, soybean, maize, cotton, strawberry, orange, grape, and peach, which are known to be involved in abiotic (Ramamoorthy et al 2008;Han et al 2018) and biotic stress responses (Pandey & Somssich 2009), seed development Figure 6. Expression of MbWRKY3 in transgenic tobacco and over-expression of MbWRKY3 in tobacco improved drought stress tolerance.…”
Section: Discussionmentioning
confidence: 69%
“…In vitro grown seedlings of M. baccata were propagated and rooted on MS medium, and transferred to Hoagland's solution for acclimation and growing for 50 d (Han et al 2018). When the seedlings had 8-9 mature leaves (fully expanded), they were exposed to air on filter paper with 20% relative humidity for dehydration and drought treatment.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited water supply enhances the production of reactive oxygen species (ROS) [68,69], and plants are protected by glutathione S-transferase (GST) and other antioxidant enzymes scavenging excessive ROS from the damage caused by ROS [70]. This is because GST comprises a large superfamily of multifunctional protein and participates in ascorbic acid (AsA)/glutathione (GSH) cycling pathways [68]. Here, probable glutathione S-transferase GST12 was significantly down-regulated under the MD treatment compared with the CK treatment.…”
Section: Reactive Oxygen Scavenging System and Ion Channel In Responsmentioning
confidence: 99%